Temperature dependence of martensite variant reorientation in stress-induced martensite aged Ni49Fe18Ga27Co6 single crystals. (15th March 2021) - Panchenko, E.; Tokhmetova, A.; Surikov, N.; Eftifeeva, A.; Tagiltsev, A.; Timofeeva, E.; Chumlyakov, Y.; Gerstein, G.; Maier, H.J.
Abstract: In the present study, the temperature dependence of martensite variant reorientation in stress-induced martensite aged at 423 K along the [110]B2 ||[100]L10 -direction Ni49 Fe18 Ga27 Co6 single crystals was investigated in compression. This martensite aging induces a rubber-like behavior with a reversible strain of up to –16.0% along the [001]B2 -direction in the temperature range from 248 K to 344 K, which is caused by L 10 -martensite variant reorientation. At higher temperatures between the forward and reverse transformation from 344 K to 382 K, the stress-induced martensite aged crystals demonstrate a two-stage stress-strain response with a reversible strain of up to –13.5%. The first stage is characterized by low critical stresses of σcr1 ≈ 1 – 15 MPa and an inverse elastocaloric effect (heat absorption) under loading. Superelasticity is observed in the second stage with σcr2 ≥ 100 MPa. In this temperature range, the martensite variant reorientation occurs through reverse and then forward martensitic transformation. Graphical abstract: Image, graphical abstract